TIRTA DALAM UPACARA PITRA YADNYA UMAT HINDU DI DESA BATU PUTIH KECAMATAN DUSUN TENGAH KABUPATEN BARITO TIMUR (Kajian Sosio Religius) - govinda, ardika (Fakultas Dharma Duta dan Brahma Widya, 2023)
Tirta or holy water is the main means of religious ceremonial activities for Hindus, as well as believed to be a medium of cleansing (pemarisudha) divine grace water (wangsuh pada) as holy water called tirta. In the context of yadnya the use of tirta as a means of pitra yadnyaceremony because of its function and meaning, then tirta in the pitra yadnya ceremony is studied using a socio-religious perspective that is routinely used by Hindus. The problem of what tirta is used in the pitra yadnya ceremony and how socioreligious tirta is in the pitra yadnya ceremony for Hindus in Batu Putih Village, Central Hamlet District, East Barito Regency, is analyzed using phenomenological and religious theories.Qualitative data on tirta used and reviews from socio-religious perspectives sourced from primary data and skunder data obtained by data collection techniques using observation, interviews and documentation analyzed using analytical methods when researching, reducing data, presenting and drawing conclusions.The result of the study is that water that has been matrai by Sulinggih or Regent is called tirtha